The Place Premium : Wage Differences for Identical Workers across the US Border - Clemens, Michael A.; Montenegro, Claudio E.; Pritchett, Lant (World Bank, Washington, DC, 2012)
This paper compares the wages of workers inside the United States to the wages of observably identical workers outside the United States-controlling for country of birth, country of education, years of education, work experience, sex, and rural-urban residence. This is made possible by new and uniquely rich microdata on the wages of over two million individual formal-sector wage-earners in 43 countries. The paper then uses five independent methods to correct these estimates for unobserved differences and introduces a selection model to estimate how migrants' wage gains depend on their position in the distribution of unobserved wage determinants. Following all adjustments for selectivity and compensating differentials, the authors estimate that the wages of a Bolivian worker of equal intrinsic productivity, willing to move, would be higher by a factor of 2.7 solely by working in the United States. While this is the median, this ratio is as high as 8.4 (for Nigeria). The paper documents that (1) for many countries, the wage gaps caused by barriers to movement across international borders are among the largest known forms of wage discrimination; (2) these gaps represent one of the largest remaining price distortions in any global market; and (3) these gaps imply that simply allowing labor mobility can reduce a given household's poverty to a much greater degree than most known in situ antipoverty interventions.